2018
DOI: 10.1590/1980-5373-mr-2017-0626
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CBD-CdS Doped with Some Rare Earths III (Eu3+,Ce3+) as Function of Synthesis Time

Abstract: Rare earths (Europium, cerium)-doped CdS nanofilms are prepared using the growth technique chemical bath deposition (CBD) at the reservoir temperature of 70±2°C varying the synthesis time in a wide range. For the rare earths doped CdS nanofilms the synthesis time was ranged from 80 to 135 min. The rare earths molar concentration was in the range 0.0≤x≤3.47, which was determined by energy dispersive X-ray spectroscopy (EDS). The X-ray diffraction (XRD) analysis reveals that CdS nanofilms showed the zinc blende … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Fig. 7 evidences, for the three representative samples, the Eg position-change in the energy axis [32]. The separation among Eg for M5, M6 and M9 (AT = 500, 600 and 900 °C, respectively) observed in Fig.…”
Section: Characterization By Absorbance Spectroscopymentioning
confidence: 64%
“…Fig. 7 evidences, for the three representative samples, the Eg position-change in the energy axis [32]. The separation among Eg for M5, M6 and M9 (AT = 500, 600 and 900 °C, respectively) observed in Fig.…”
Section: Characterization By Absorbance Spectroscopymentioning
confidence: 64%
“…7b-c present evidences of both CP's, these results support the previous analysis that the produced TiO2-NF's have a anatase-rutile mixed phase polycrystalline structure, caused by thermal heating in the 600-800 °C AT-range as observed by Raman scattering and XRD. [28]. The separations among Eg's for the M5, M6 and M9 samples (AT = 500, 600 and 900 °C, respectively) illustrated in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The effect of nano (CdS) of serum GPT and GOT enzymes activity was investigated in this study, the biochemical tests revealed that nanoparticles caused inhibitory effects on GPT and GOT enzymes. The relationship between nanoparticles concentration versus the activity of enzymes as shown in figure (5)and figure (6) for GPT and GOT respectively. These results observed that any increase in nano concentrations caused decreases in activation of enzymes and increases in inhibition percentage.…”
Section: The Effect Of Cds Nanoparticles On Gpt and Got Enzyme Activitymentioning
confidence: 99%
“…Cadmium sulphide nanoparticle was used in different application this as gas sensor, solar cell, photochemical catalysis, detectors for laser and biological labels. Preparation of Cadmium sulphide nanoparticle could be done by fresh chemical reaction, microwave heating [1,2], sol-gel method [3], more of the researcher prepared Cadmium sulphide nanoparticles in the existence of unlike surface material and cover agents [4,5,6]. Cadmium sulfide thin film have attract increasing interest, in new year's because of its widely direct band gap energies, electrical properties, optical and stability, different ways, that as chemical vapor deposition, spray pyrolysis and sputtering, and successive ionic coat adsorption and reaction had use for depositing Cadmium sulfide films.…”
Section: Introductionmentioning
confidence: 99%